2023
DOI: 10.1128/mbio.02384-22
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Distribution of Proton Motive Force in Nonheritable Antibiotic Resistance

Abstract: Bacterial cells with low PMF may survive antibiotic stress due to dormancy, which favors nonheritable resistance without genetic mutations or acquisitions. On the other hand, cells with high PMF are less tolerant, as PMF helps in the uptake of certain antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 69 publications
1
11
0
Order By: Relevance
“…The cells were then suspended in lethal concentrations of ampicillin for three hours (see Materials and Methods ). A significant fraction of the cells tolerated the ampicillin exposure and several cells retained motility, consistent with earlier studies ( 32, 34, 53 ). We again washed the tolerant cells to remove ampicillin and loaded them into the microfluidic chamber while simultaneously observing the channels.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…The cells were then suspended in lethal concentrations of ampicillin for three hours (see Materials and Methods ). A significant fraction of the cells tolerated the ampicillin exposure and several cells retained motility, consistent with earlier studies ( 32, 34, 53 ). We again washed the tolerant cells to remove ampicillin and loaded them into the microfluidic chamber while simultaneously observing the channels.…”
Section: Resultssupporting
confidence: 90%
“…Our recent study suggests that rifampicin induces a bifurcation of the tolerant population: nearly one out of three tolerant cells continued to swim rapidly in lethal concentrations of ampicillin for several hours, while the rest were nonmotile ( 32 ). As motility requires the PMF, which also produces ATP during aerobic respiration, this suggested that a significant fraction of the tolerant cells might not be dormant.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations